PENGARUH STRATEGI PROBLEM-BASED LEARÂNING (PBL) TERHADAP MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN FIQIH DI MA. KHOZINATUL â€˜ULUM BLORA JAWA TENGAH - Syaifulloh, Ahmad (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2016)
AbstractStrategy of problem-based learning is a teaching strategy that is student-centered in a manner that exposes student to the various problems encountered in life to be analyzed and synthesized in an attempt to find solutions or answers. Experimental research design used is True Experimental Design with a pretest-posttest form Control Group Design. Populations are normal and have the same homogeneity thus making the two groups of samples using cluster random sampling technique. The data source of research is learners class XI IPS1 and XI IPS2 MA. Khozinatul ‘Ulum Blora Central Java, principals, teachers, employees and documents madrasah. The results showed that: There is the effect of problem-based learning strategies to motivate students; and there is the effect of problem-based learning strategies on learning outcomes students. In addition to increased student learning outcomes in the cognitive aspects of the above, there is also an increase in the study of students in the affective and psychomotor aspects.Keywords: Problem-based learning, motivation, achievement.